Factor Analysis of Customer Decisions to Buy Neeyoo Fashion Retail Products in Surabaya - I. Babuta, Yoddie Yanuar; Harianto, Eric (KnE Social Sciences, 2021)
This study analyzed what factors shape consumers’ decisions to purchase Neeyoo fashion store products, so as to prepare corporate strategies to increase the amount of company turnover. This research used the Exploratory Factor Analysis (EFA) method. The 107 participants were consumers of Neeyoo stores. The study used a survey questionnaire with 5% error based on the Exploratory Factor Analysis. 36 initial variables were included and 7 factors were found that shaped consumer purchasing decisions: service and managerial performance, the right product selection, promotion media design and price according to quality, location / business ease, product suitability to consumer needs, in-store presentation, and reference group. Service and managerial performance had the highest variation values at 35.949%. The results showed that improving customer service can increase turnover at Neeyoo stores. Keywords: retail, fashion, factor analysis, purchasing decisions